2018
DOI: 10.4049/jimmunol.1701605
|View full text |Cite
|
Sign up to set email alerts
|

Oral NaHCO3 Activates a Splenic Anti-Inflammatory Pathway: Evidence That Cholinergic Signals Are Transmitted via Mesothelial Cells

Abstract: We tested the hypothesis that oral NaHCO intake stimulates splenic anti-inflammatory pathways. Following oral NaHCO loading, macrophage polarization was shifted from predominantly M1 (inflammatory) to M2 (regulatory) phenotypes, and FOXP3CD4 T-lymphocytes increased in the spleen, blood, and kidneys of rats. Similar anti-inflammatory changes in macrophage polarization were observed in the blood of human subjects following NaHCO ingestion. Surprisingly, we found that gentle manipulation to visualize the spleen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…Several paradigms have been proposed to suppress a pathological immune response. Oral NaHCO 3 dosing in rats stimulates an anti-inflammatory response; this effect could be harnessed to prevent tissue damage in autoimmune diseases such as rheumatoid arthritis [336] . One preliminary study in mice even suggests that oral NaHCO 3 dosing could be useful to suppress peanut allergy [337] .…”
Section: Applications By Organ Systemmentioning
confidence: 99%
“…Several paradigms have been proposed to suppress a pathological immune response. Oral NaHCO 3 dosing in rats stimulates an anti-inflammatory response; this effect could be harnessed to prevent tissue damage in autoimmune diseases such as rheumatoid arthritis [336] . One preliminary study in mice even suggests that oral NaHCO 3 dosing could be useful to suppress peanut allergy [337] .…”
Section: Applications By Organ Systemmentioning
confidence: 99%
“…They demonstrated that alongside the progressive increase in blood pressure and histological renal injury, there was a continual increase in renal macrophages, clearly demonstrating sustained innate immune system activation in the kidney. A recent study by Ray et al (31) demonstrated that the macrophage polarization in the kidneys of Dahl SS rats on a high-salt diet can be shifted from an M1 phenotype toward an M2 phenotype by oral sodium bicarbonate intake.…”
Section: Dahl Ss Ratsmentioning
confidence: 99%
“…The effects of extracellular acidosis on immune cells have been covered by multiple studies [ 39 ], but except for indirect associations, a pH-dependent modulation of the immune response in CKD has not been shown. Oral HCO 3 − supplementation given to a hypertensive kidney disease rat model activated polarization of macrophages to the anti-inflammatory M2 type, suggesting that acidosis might regulate splenic immune responses in CKD [ 40 ].…”
Section: Introductionmentioning
confidence: 99%